Debt Management Programme or Plan (DMP) and financial or credit counselling in Malaysia, Thailand and Indonesia - Ruzita Azmi; Rachma Indriyani (United Nations Research Institute for Social Development (UNRISD), 2024)
The study focuses on programmes that offer assistance and guidance to those facing financial difficulties in emerging economies in Southeast Asia, specifically Malaysia, Thailand and Indonesia. This research aims to achieve the following objectives: (i) evaluate the Debt Management Programme or Plan (DMP) and financial or credit counselling in Malaysia and compare it with similar programmes in Thailand and Indonesia; (ii) analyse the effectiveness of DMP and financial or credit counselling in addressing the issue of indebtedness; and (iii) highlight how these programmes can prevent bankruptcy. The findings of this study reveal that among the three jurisdictions, only Malaysia, under the purview of its Central Bank, has formed the Credit Counselling and Debt Management Agency, commonly referred to as Agensi Kaunseling dan Pengurusan Kredit (AKPK), to provide advice and support to individuals who are struggling with financial issues. While Thailand and Indonesia do not have organisations similar to Malaysia's AKPK, they do have similar programmes to assist debtors with managing their debts. These programmes include DMP and credit counselling, whereas financial education, financial literacy and financial behaviour all fall under the umbrella of financial management. In today's unpredictable economy, it is widely acknowledged that financial education encompassing financial literacy and management life skills is crucial. Alongside this, DMP is viewed as a helpful tool for repaying creditors. With the aid of a counsellor, debtors can negotiate a repayment plan and avoid bankruptcy.
Keywords: 330